Spiritual Harmony in Boarding Schools: The Influence of Technology-Based Learning Models to Improve Students' Religious Character and Wellbeing - Goselfa, Limason; Shodiq, Sadam Fajar (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
The objective of this study is to investigate the impact of technology-based learning models, represented as the independent variable (X), on the enhancement of religious character (Y1) and wellbeing (Y2), which serve as the dependent variables. This study used a quantitative research methodology, utilising a sample size of 259 participants who accurately completed the survey out of a total of 289 participants. Samples were collected utilising a method of random sampling. The data collected from 259 questionnaires, each including 31 statement items, was deemed legitimate based on a reliability value exceeding 0.7, indicating good reliability. The employed methodology for data analysis is basic regression analysis. The data analysis results indicate that variable (X) has a significant impact on increasing variables (Y1) and (Y2). This analysis is conducted using hypothesis testing. The original sample value (Y1) is determined to be 0.452. The t-statistic is calculated to be 5.236, which is more than the critical value of 1.96 at the 5% significance level. Additionally, the p-value is found to be 0.000, which is less than the significance level of 0.05. At the 5% level, the t-statistic of 5.007 for the (Y2) sample value of 0.442 is greater than 1.96. The p-value of 0.000 is statistically significant, as it is lower than the threshold of 0.05. The coefficient of determination (R Square) indicates a value of 0.692, which is comparable to 69.2%. This means that 69.2% of the variation in the dependent variable can be explained by the independent factors. The other variables, accounting for 30.8%, have an influence on the dependent variable. These results indicate that technology-based learning approaches have the potential to positively impact students' religious character and wellbeing.